Destabilizing Gender Norm in Contemporary Indonesian Discourses - Wening Udasmoro (MOZAIK HUMANIORA, 2017)
Being a man and a woman are not a question of nature but a system of culture where it is shaped not only by the cultural regime itself, but also by the different political regimes. The change of different political regimes in Indonesia shape the separation of man and woman through a very strict separation into the value of masculine and feminine. However, this dichotomy has been progressively defined in the social practice, especially in the media, literature and everyday discourses, where people start to claim the diversity of gender seen as part of social reality.  People start to openly express their identity as gay, lesbian or transgender as part of their personal and social experiences. The questions posed are firstly what are the aspects destabilized in the discourses related to gender orientation? Secondly, what are the aspects changed and maintained in that process of destabilization? In which argument the process of destabilizing gender norm is done during the reformasi era? This article attempts to show how the gender norm longtime believed as an established gender orientation of man and woman is destabilised by different social actors in Indonesia in order to claim the diversity of gender with the interchangeable value of masculine and feminine in the society.